SAT0640-HPR Understanding The Importance of A Patient's Role in The Management of RA: Physician- and Patient-Based Survey Results Developed by The RA Narrative Advisory Panel. (15th July 2016) - Dikranian, A.; Galloway, J.; Kekow, J.; Zerbini, C.A.F.; de la Vega, M.; Lee, G.; Maniccia, A.; Bananis, E.; Ponce de Leon, D.; Gibofsky, A.
Abstract : Background: RA is a chronic, debilitating condition for which there is no cure. Objectives: To identify and better understand the perspectives of both healthcare providers (HCPs) and patients (pts) regarding RA treatment and management, using data from an HCP- and a pt-based survey, developed by the RA NarRAtive global advisory panel. Methods: The RA NarRAtive initiative comprises an advisory panel of 39 RA experts from 17 countries. An HCP-based (16 countries) and a pt-based survey (15 countries), designed by the working group, were fielded online between Aug-Oct 2015, and Sept 2014-Jan 2016, respectively. Results are presented from pts treated by a rheumatologist. All respondents are from the same 15 countries. Results: 3987 pts responded (1653 were currently managed by a rheumatologist): mean age 51.5 years (yrs), 64% female, median time since diagnosis 7 yrs; respondents represented a wide spectrum of disease activity: moderate to severe (30%; 501) and severe (11%; 176). In the HCP survey, 90% of respondents were satisfied with their communications with pts but 68% acknowledged, "I wish my pts and I talked more about goals and treatment". In the pt survey, 53% of pts acknowledged that dialogue with the HCP would optimise the management of their RA. 61% of all respondents felt uncomfortable raising concerns or fears to their HCP. 93% of HCP respondents discuss quality of life (QoL) issues with their pts including impact of RA on ability to work, participation in activities and lifestyle goals. 86% discuss treatment-related issues including adherence to therapy, medication preferences and whether pts seek treatment from other HCPs. The most common topics that pts report worrying about (and HCPs believe their pts worry about) are similar but these factors were ranked differently between pts and HCPs: the number one factor for pts is the impact on QoL; the number one factor for HCPs is prescription side effects. HCPs and pts have similar views on what they would most like to change about currently available RA medications, ie severity and number of side effects, cost and efficacy. HCPs highlighted disease remission as a treatment goal; while pts more frequently referred to symptom reduction. Overall, 88% of HCPs agreed that pts involved in making treatment decisions tend to be more satisfied with their treatment experience; 74% felt that pts who are not involved are less likely to adhere to treatment. Setting treatment goals with pts and agreement on the treatment plan are considered important by 78% and 79% of HCPs, respectively, as is being able to have an open dialogue (86%). Conclusions: Differences between treatment goals set by pts and HCPs were reported, highlighting the importance of an open pt-HCP dialogue in the successful management of RA. These findings could help improve adherence and pt satisfaction with their disease management. Acknowledgement: These surveys were funded by Pfizer Inc. Editorial support was provided by S Johnson of CMC and funded by Pfizer Inc. Disclosure of Interest: A. Dikranian Consultant for: Pfizer Inc, AbbVie, Speakers bureau: Pfizer Inc, AbbVie, J. Galloway Consultant for: Pfizer Inc, J. Kekow: None declared, C. A. Zerbini Grant/research support from: Pfizer Inc, Amgen, Sanofi, Novartis, Merck, Eli Lilly, GSK, Celltrion, Consultant for: Pfizer Inc, Eli Lilly, Sanofi, M. de la Vega Consultant for: Pfizer Inc, G. Lee Consultant for: Pfizer Inc, AbbVie, A. Maniccia Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, E. Bananis Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, D. Ponce de Leon Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, A. Gibofsky Shareholder of: AbbVie, Amgen, BMS, GSK, J&J, Pfizer Inc, Consultant for: AbbVie, Antares, Celgene, Horizon, Iroko, Medac, Novartis, Pfizer Inc, Relburn, Samumed, Speakers bureau: AbbVie, Amgen, Celgene, Pfizer Inc